Seasonal Temperature Differentially Modulates the Immunotranscriptomic Performance in Atlantic Salmon Skin in Response to Natural Caligus Rogercresseyi Infestation in Open-Ocean Cages - Reyes-Lopez, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Chile is the second-largest producer of Atlantic salmon (Salmo salar), a key industry facing challenges such as infestations by Caligus rogercresseyi, which cause significant economic losses. However, there are no studies exploring how environmental variables in marine culture centers affect salmon’s immune response, considering their poikilothermic characteristics. This study analyzed the effect of the seasonal temperature on the skin transcriptome of Atlantic salmon infested with C. rogercresseyi in fjord-based farms in the Aysén Region during autumn and spring. Two different centers were analyzed (autumn: Farm-A; spring: Farm-S) to ensure the same age of the fish sampled in each season. RNA sequencing (RNA-seq) and functional network analysis revealed notable seasonal transcriptomic differences. In autumn, 253 differentially expressed genes (DEGs) were found, primarily associated with stress response and negative regulation of T-cell proliferation, suggesting an impaired response against the ectoparasite. In spring, 103 DEGs were detected, associated with protein synthesis and the activation of immune mechanisms, including complement activation, granulocyte chemotaxis, and antigen presentation. This is the first study to evaluate the transcriptomic response of healthy skin in C. rogercresseyi-infested salmon under farming conditions, highlighting the importance of considering seasonal variations for the development of more effective management strategies in the aquaculture industry. © 2025 by the authors.